Latitudinal and Longitudinal Trends of Seed Traits Indicate Adaptive Strategies of an Invasive Plant - Zhou, Lifeng; Yu, Hongwei; Yang, Kaiwen; Chen, Li; Yin, Wandong; Ding, Jianqing (Frontiers in Plant Science, 2021)
Invasive plants may change their seed traits to adapt to the environment and facilitate their performance. Studies on variation in seed traits among populations of an invader along latitudes/longitudes may assist in revealing how invasive plants cope with variable climates. In this study, we collected seeds of 26 populations of the global invasive plant Ambrosia artemisiifolia along ranges spanning 23° latitudes and 20° longitudes that are highly correlated in its invasive range in China. We measured over 20 seed traits, including seed morphology, phytohormone, nutrients, and germination, and investigated how the climate along the latitudes affects those traits. We found that germination time was significantly delayed with increasing latitude and longitude, while the reversed patterns were true for the germination rate. From low to high latitude, seed size, abscisic acid, and fatty acid were increased, likely affecting seed germination. Our analysis further demonstrated that temperature is the dominant driver of the variability in seed traits and germination. Germination rates of larger seeds in cold ranges were lower, while smaller seeds from warm ranges germinated faster, likely indicating adaptive strategies of the invasive plant in seed trait functional ecology. Together, our findings provide new insights into understanding the seed adaptation strategies during the invasion process and the underlying physiological and biochemical mechanisms involved.